Modeling of the Microwave Heating-Toasting Time-Related Variables and Characterization of Non-Isothermal Rheological Properties of Floury and Sweet Specialty Maize Kernels - Osorio-Lira, F (Elsevier B.V., 2022)
The three primary floury and sweet maize types, with specialty kernels to make entire ready-to-eat maize, and packed in sealable paper envelopes, were the experimental units (150 g of raw kernels) to model the effect of the microwave heating-toasting (2450 MHz microwave oven, 492 W, times 0, 78, 156, 234, 312, and 390 s) on time-related variables and characterize the non-isothermal rheological properties. Pauses every 60 s for a rapid manual shaking compensated for non-uniformity of microwave volumetric heating. Surface color difference (ΔE*), internal porosity, milling average particle size, and flour hydration properties displayed curves adequately described by simple and nonlinear regression models. The milling particle size, hydration properties, and rheological parameters illustrated floury and sweet kernel differences ascribed to their proximal composition. Onset and peak temperatures depended on maize types and showed a little variation attributed to microwave heating-toasting times. The elastic/viscous modulus ratio increased in floury maize. It decreased in sweet maize, unveiling rheological differences associated with microwave heating-toasting time effect on the contrasting structure of floury and sweet specialty Andean maize kernels used for toasting. © 2022